Search balance and product and process innovations - Martin Backfisch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
Firms' search for external knowledge is one aspect of knowledge integration in the innovation process. The literature has investigated innovation and the breadth of search in different information channels. We introduce the concept of search balance reflecting the heterogeneity of a firm's knowledge base. Results from German Community Innovation Survey data shows that search balance is positively connected to the introduction of product as well as process innovations. The connection is stronger for process innovations. The relative balance between all information sources used by firms is important for process innovations, but less so for product innovations. Product innovations rely on specific search directions where internal or market-based knowledge is found, offering an alternative to balanced search. Such an alternative does not exist for process innovations such that knowledge from specific information channels has to be accompanied by balanced search in other channels to be successfully used for process innovations.
Keywords: O31; O32; 330; Openness; knowledge sources; innovative search; search balance; innovation; innovation performance